2020
DOI: 10.1371/journal.pone.0243982
|View full text |Cite
|
Sign up to set email alerts
|

How does rising housing price affect the health of middle-aged and elderly people? The complementary mediators of social status seeking and competitive saving motive

Abstract: Under the backdrop of China’s aging population and continuous rising housing price and base on theories pertaining to social status seeking, marriage matching and intergenerational family relationships, use the 2010 and 2014 CFPS national survey micro data, we examine the impact of rising housing price on the health of middle-aged and elderly people and the underlying mechanisms. Rising housing price has a significant negative impact on the health of middle-aged and elderly people, and this effect is also refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Nine studies analyzed the impact of housing prices on physical health—utilizing various measures of physical health, including objective assessments of physical health (e.g., body mass), self-rated physical health assessments, reports of specific health conditions (e.g., COVID-19), reported health behaviours (e.g., alcohol use, smoking), and mortality ( [ 24 , 28 , 29 , 37 , 44 , 30 , 36 , 38 , 39 ]). Seven studies included both physical and mental health measures as their outcome variable [ 19 , 20 , 23 , 26 , 27 , 34 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies analyzed the impact of housing prices on physical health—utilizing various measures of physical health, including objective assessments of physical health (e.g., body mass), self-rated physical health assessments, reports of specific health conditions (e.g., COVID-19), reported health behaviours (e.g., alcohol use, smoking), and mortality ( [ 24 , 28 , 29 , 37 , 44 , 30 , 36 , 38 , 39 ]). Seven studies included both physical and mental health measures as their outcome variable [ 19 , 20 , 23 , 26 , 27 , 34 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neighborhood housing price data obtained from the Ministry of Land, Infrastructure, and Transport. Supplementary data obtained from the Seoul Metropolitan Government’s information disclosure system Analysis : Mapping distribution of all-cause mortality and housing prices using pooled OLS models Outcome: All-cause mortality using Ministry of Interior and Safety data Explanatory: Median houses price using the Ministry of Land, infrastructure, and transport data in Korea Confounding : Poverty rate; Population density; Business workers; Number of nearby subway stations; Movement to other neighborhoods; Social and Public Health Policies Mediating/Moderating: Education; Access to resources; Socioeconomic development of area -A 1% increase in housing prices was related to a 0.05% decrease in all-cause mortality Hamoudi & Dowd (2014) [ 25 ] N: 4207 people Location: United States Timeframe: mid 1990s to mid 2000s Data: Longitudinal study using data from the Health and Retirement Study (HRS), and housing data from DataQuick Analysis : Regression modeling, results reported as regression coefficients Outcome : Depression measured with CES-D; Beck Anxiety inventory; Mroczeck/Korarz Positive Affect Inventory; Mrocczek/Kolarz Negative Affect Inventory Explanatory: Housing values from DataQuick Confounding: Home value at baseline; Total non-housing wealth; Share of housing equity at baseline; Birth year; Sex; Area of residence; Self-rated health; Indicators for smoking and exercise at baseline; Share of housing equity at baseline; Study cohort Mediating/Moderating: Homeowner vs. renter; Wealth; Local area improvements - Movement from 10th-90th percentile for homeowners in terms of housing appreciation is associated with: - decreased likelihood of anxiety in homeowner females (-19.6), and increased likelihood of anxiety in male homeowners (1.7) - (b) decreased depression risk among female homeowners (-2.3), and decreased depression among male homeowners (-1.3) - decrease likelihood of negative effect among female homeowners (-3.5) and decrease likelihood in negative effect for male homeowners (-7.7) - increase in likelihood of positive affect for female homeowners (5.9), and male homeowners (1.9) - increase in likelihood of anxiety for female renters (2.9), and increase in likelihood for male renters (68.2) - increase in likelihood of depression for female renters (15.7), and increase in likelihood for male renters (16.8) - increase in likelihood of negative effect for female renters (27.7) and increase for male renters (35.8) - decrease in likelihood for positive affect among female renters (-18.7) and increase for male renters (8.3) Yuan et al (2020 ) [ 26 ] N: 34,000 people Location: China (25 provinces) Timeframe: 2010 and 2014 Data: Cross sectional study using data from the 2010 and 2014 China Family Panel Study Analysis: Regre...…”
Section: Methodsmentioning
confidence: 99%
“…Residents' increased leverage has led to a lack of external financial resources, and companies' financing channels have become narrower. It is more difficult for financial institutions to mobilize resources to provide funds for companies with high financing constraints (Yuan et al, 2020). Companies with low financing constraints have abundant assets, relatively strong operating income, and debt solvency, which can obtain more loan opportunities and lower financing costs.…”
Section: The Estimated Results Of Heterogeneity Analysismentioning
confidence: 99%
“…The ratio of corporate noncurrent liabilities to total liabilities is used to measure the level of corporate debt. The proportion of corporate financial assets to total assets is used to measure the degree of corporate financialization (Yuan et al, 2020). The proportion of corporate interest expenses to new debt is used to measure the degree of corporate zombification.…”
Section: Other Variablesmentioning
confidence: 99%
“…However, there is a lack of such research in China, the world's second largest economy, which is not commensurate with the current world pattern. As the largest developing country in the world, China's experience in housing reform, living condition improvement, and health improvement hold important implications and value for the vast number of developing countries [28,29]. Therefore, empirical testing of relevant hypotheses about the relationship between living conditions and health in China has important theoretical and practical value.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%